Phylogenetic Analysis and Spread of HPAI H5N1 in Middle Eastern Countries Based on Hemagglutinin and Neuraminidase Gene Sequences - Laith N. AL-Eitan; Diana L. Almahdawi; Iliya Y. Khair (Viruses)
Highly pathogenic avian influenza (HPAI) A/H5N1 viruses threaten animal and human health worldwide. The first documented cases in the Middle East were reported in 2005; however, despite extensive phylogenetic studies, there is limited information on the transmission dynamics of the virus within this region. We analyzed HA and NA gene sequences from various hosts to address this gap and to understand the virus’s spread and evolution in the Middle East. We hypothesized that H5N1 transmission exhibits host-specific or geographically influenced clade structures in this region. This study traced transmission pathways of HPAI A/H5N1 through a phylogenetic and amino acid sequence analysis of HA and NA gene segments from isolates across different hosts in Middle Eastern countries, using the MUSCLE algorithm for alignments and MEGA11 software for phylogenetic analysis. Sequences were selected from NCBI’s virus database based on geographic and host diversity, including those from birds, humans, and other mammals, and were collected at different time points, predominantly after the early 2000s. An amino acid phylogenetic tree was also constructed to examine the conservation of key HA and NA protein residues, identifying distinct clades linked to specific countries and host species, suggesting a possible interspecies transmission and cross-border spread distinct between Egypt and neighboring countries. These findings underscore the role of migratory birds in regional transmission and point to the need for more targeted surveillance and biosecurity efforts, offering more genomic insights into the spread of HPAI A/H5N1 and contributing valuable information for future prevention strategies.